2015
DOI: 10.4329/wjr.v7.i7.149
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted and diffusion-tensor imaging of normal and diseased uterus

Abstract: Owing to technical advances and improvement of the software, diffusion weighted imaging and diffusion tensor imaging (DWI and DTI) greatly improved the diagnostic value of magnetic resonance imaging (MRI) of the pelvic region. These imaging sequences can exhibit important tissue contrast on the basis of random diffusion (Brownian motion) of water molecules in tissues. Quantitative measurements can be done with DWI and DTI by apparent diffusion coefficient (ADC) and fractional anisotropy (FA) values respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…[54][55][56] More recently, the use of diffusion tensor imaging has also been explored in uterine and gynecological disorders like endometriosis, malignancies, and uterine fibroids, suggesting great potential in the use of these techniques in gynecological conditions. 57,58 Their diagnostic potential remains to be definitively evaluated; however, the one study that investigated diffusion tensor imaging for its diagnostic potential showed superior accuracy over conventional MRI. 16 There are several limitations which may impact our results.…”
Section: Correlation With Clinical Outcomesmentioning
confidence: 99%
“…[54][55][56] More recently, the use of diffusion tensor imaging has also been explored in uterine and gynecological disorders like endometriosis, malignancies, and uterine fibroids, suggesting great potential in the use of these techniques in gynecological conditions. 57,58 Their diagnostic potential remains to be definitively evaluated; however, the one study that investigated diffusion tensor imaging for its diagnostic potential showed superior accuracy over conventional MRI. 16 There are several limitations which may impact our results.…”
Section: Correlation With Clinical Outcomesmentioning
confidence: 99%